Diets and Seasonal Ingestion Rates of Aurelia coerulea (Cnidaria: Scyphozoa) Polyps by in situ Feeding Experiments in Jiaozhou Bay, China - Pengpeng, Wang; Fang, Zhang; Dongjie, Guo; Song, Sun (Frontiers in Marine Science, 2021)
The benthic scyphopolyp population is an important stage in the scyphozoan lifecycle. Nevertheless, few studies have detailed the natural feeding and quantified the energy flux of polyps based on field research. To better understand the scyphopolyp natural diet and seasonal variation patterns in the ingestion rate, in situ feeding experiments were conducted on Aurelia coerulea polyps in Jiaozhou Bay, China from August 2018 to April 2019. The diet of A. coerulea polyps was determined by gut content analysis. Digestion rates were also measured. Ingestion rates, based on the gut contents and digestion rates, were assessed monthly. Copepods, copepod nauplii and ciliates were identified in the guts of A. coerulea polyps. Copepods with the bulk of total prey intake in number are an important source of nutrition for A. coerulea polyps in Jiaozhou Bay. Prey capture of A. coerulea polyps (prey polyp-1) varied among months, and was highly dependent upon the abundance of planktonic prey in the habitat. Copepods and copepod nauplii were digested more rapidly as temperature increased. Carbon weight-specific ingestion rate exhibited an obvious seasonal change, with the mean value of 0.13 ± 0.12 μg C μg C-1 d-1. More rapid digestion of prey at higher temperatures and larger prey availability would cause a higher ingestion rate in polyps. Scyphopolyps are widely distributed predators in littoral ecosystems and they may play an important role in plankton-benthos coupling by transferring energy from the water column to the benthos. Massive scyphopolyps blooms may influence pelagic ecosystems.